2023
DOI: 10.3390/cells12050812
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of LKB1 by PDK1 Inhibits Cell Proliferation and Organ Growth by Decreased Activation of AMPK

Abstract: The master kinase LKB1 is a key regulator of se veral cellular processes, including cell proliferation, cell polarity and cellular metabolism. It phosphorylates and activates several downstream kinases, including AMP-dependent kinase, AMPK. Activation of AMPK by low energy supply and phosphorylation of LKB1 results in an inhibition of mTOR, thus decreasing energy-consuming processes, in particular translation and, thus, cell growth. LKB1 itself is a constitutively active kinase, which is regulated by posttrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In summary, we revealed that the polybasic motif of LKB1 can establish stable, albeit highly dynamic, binding with membranes with low amounts of PA. This suggests that farnesylation of LKB1 is not specifically required for stable association of LKB1 with membranes, which has been supported by in vivo experiments (Dogliotti et al 13,35 ). Furthermore, the LKB1-membrane interaction revealed interesting mutual effects of the protein and anionic lipids, such as proteins' structural modifications and agglomeration of PAs, providing microscopic and thermodynamic insights into the interaction of LKB1 with membranes containing PAs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In summary, we revealed that the polybasic motif of LKB1 can establish stable, albeit highly dynamic, binding with membranes with low amounts of PA. This suggests that farnesylation of LKB1 is not specifically required for stable association of LKB1 with membranes, which has been supported by in vivo experiments (Dogliotti et al 13,35 ). Furthermore, the LKB1-membrane interaction revealed interesting mutual effects of the protein and anionic lipids, such as proteins' structural modifications and agglomeration of PAs, providing microscopic and thermodynamic insights into the interaction of LKB1 with membranes containing PAs.…”
Section: Discussionmentioning
confidence: 67%
“…Schneider S2R+ cells on coverslips were transfected with GFP-LKB1 variants under a ubiquitous promoter (Ubi::GFP-LKB1) using FUGENE (Promega). 35 48 h after transfection, cells were fixed with 4% paraformaldehyde in PBS pH7.4 for 20min. Subsequently, cells were washed three times with PBS and nuclei were labelled with DAPI for 20min.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…In summary, we revealed that the polybasic motif of LKB1 can establish stable, albeit highly dynamic, binding with membranes with low amounts of PA. This suggests that farnesylation of LKB1 is not specifically required for stable association of LKB1 with membranes, which has been supported by in vivo experiments (Dogliotti et al 13,40 ). Furthermore, the LKB1-membrane interaction revealed interesting mutual effects of the protein and anionic lipids, such as proteins' structural modifications and agglomeration of PAs, providing microscopic and thermodynamic insights into the interaction of LKB1 with membranes containing PAs.…”
Section: ■ Conclusionmentioning
confidence: 67%
“…Schneider S2R+ cells on coverslips were transfected with GFP-LKB1 variants under a ubiquitous promoter (Ubi::GFP-LKB1) using FUGENE (Promega). 40 48 h after transfection, cells were fixed with 4% paraformaldehyde in PBS pH 7.4 for 20 min. Subsequently, cells were washed three times with PBS, and nuclei were labeled with DAPI for 20 min.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…The prediction result of phosphorylation sites showed that the PTHLH protein may contain phosphorylation sites for protein kinases such as PKA, PKC, PKG and p38 MAPK. Protein phosphorylation, as a widespread reversible post-translational modification in biology, is involved in gene expression regulation, signal transduction, and is closely related to cell proliferation, apoptosis and development of cancer [22][23][24][25]. Inhibitors of p38 MAPK, PKC can reduce synthesis and secretion of PTHLH, speculating that PTHLH protein may be affected by the comprehensive action of various kinases to influence protein phosphorylation and its activity, thereby regulating the expression of the…”
Section: Discussionmentioning
confidence: 99%